The Effect of Debt to Equity Ratio, Return on Assets, and Inflation Level on Stock Prices: Empirical Study of Manufacturing Firms in the Consumer Good Industry Listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 - Wahyudi, Rahmat; Fatimah, Fatimah; Ladewi, Yuhanis (International Journal of Finance Research, 2025)
This study aims to determine the effect of the debt-to-equity ratio, return on assets, and inflation rate on stock prices using an empirical analysis of manufacturing companies in the consumer goods sub-industry listed on the Indonesia Stock Exchange (IDX). The object of this study is 52 manufacturing companies in the consumer goods sub-industry, spanning the period from 2018 to 2023. The sample in this study was 47 manufacturing companies in the consumer goods sub-industry. The sampling technique used in this study is Purposive Sampling. In this study, the sample consisted of companies that published financial statements and reported losses for the years 2019 -2023.  The results of this study indicate simultaneously and partially (1) debt to equity ratio, return on assets, and inflation rate together have a positive and significant effect on stock prices (2) debt to equity ratio does not affect and is significant on stock prices (3) return on assets does not affect and is significant on stock prices (4) Inflation rate does not affect and is significant on stock prices.